TEOLOGI KRISTEN DALAM PERBEDAAN ALIRAN: UPAYA MEMAHAMI KERAGAMAN DALAM KESATUAN IMAN - Hilbreth Parende Kayang; Vhaganza Aditya Pasally, Maurice Mercy Ra’bang, Vesiansi Nona Turu, Yunirma (ADISAM PUBLISHER, 2025)
This article discusses the dynamics of differences in Christian theology and efforts to build unity of faith amidst this diversity, especially in the Indonesian context. Theological differences that emerged from the long history of the church such as the Reformation, Catholic tradition, Protestantism, Evangelicalism, and Pentecostalism have shaped the diversity of the face of global and local Christianity. This study uses a qualitative descriptive approach with a literature study of Indonesian-language theological sources to explore the roots of the differences, the characteristics of each stream, and their contributions to the life of faith of Christians. This article also highlights the challenges in theological dialogue between streams, including exclusivism and minimal understanding across traditions. However, behind these challenges lies a great opportunity to build cooperation, dialogue, and shared testimony. In the context of a pluralistic and diverse Indonesia, unity of faith can be developed through inclusive theological education, cross-church cooperation, and the development of contextual theology that is relevant to local culture and reality. Unity in the Christian faith does not mean uniformity, but rather the recognition of Christ as the center of faith that unites all differences. With a spirit of love and humility, the church in Indonesia is called to be an example in caring for diversity and declaring it as a shared strength